Beyond “somatization” and “psychologization”: symptom-level variation in depressed Han Chinese and Euro-Canadian outpatients - Dere, Jessica; Sun, Jiahong; Zhao, Yue; Persson, Tonje J.; Zhu, Xiongzhao; Yao, Shuqiao; Bagby, R. Michael; Ryder, Andrew G. (Frontiers in Psychology, 2013)
The finding that people of Chinese heritage tend to emphasize somatic rather than psychological symptoms of depression has frequently been discussed in the culture and mental health literature since the 1970s. Recent studies have confirmed that Chinese samples report more somatic and fewer psychological depression symptoms compared to ‘Western’ samples. The question remains, however, as to whether or not these effects are attributable to variation in all the constituent symptoms or to a subset. If the latter, there is the additional possibility that some symptoms might show a divergent pattern. Such findings would have implications for how cultural variations in symptom presentation are interpreted, and would also inform the cultural study of affective experiences more broadly. The current study addressed these issues in Chinese (n = 175) and Euro-Canadian (n = 107) psychiatric outpatients originally described by Ryder et al. (2008). Differential item functioning (DIF) was used to examine whether specific somatic and psychological symptoms diverged from the overall patterns of cultural variation. Chi-square analyses were used to examine atypical somatic symptoms (e.g., hypersomnia), previously neglected in this literature. No DIF was observed for the typical somatic symptoms, but Euro-Canadians reported greater levels of atypical somatic symptoms, and showed higher rates of atypical depression. DIF was observed for psychological symptoms - the Chinese reported high levels of ‘suppressed emotions’ and ‘depressed mood’, relative to their overall psychological symptom reporting. Chinese outpatients also spontaneously reported ‘depressed mood’ at similar levels as the Euro-Canadians, contrary to prevailing ideas about Chinese unwillingness to discuss depression. Overall, the findings provide a more nuanced picture of how culture shapes symptom presentation and point towards future studies designed to unpack cultural variation in narrower subsets of depressive symptoms.